2018
DOI: 10.18632/aging.101627
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic extract of Tamarix Gallica attenuates hyperhomocysteinemia induced AD-like pathology and cognitive impairments in rats

Abstract: Although few drugs are available today for the management of Alzheimer’s disease (AD) and many plants and their extracts are extensively employed in animals’ studies and AD patients, yet no drug or plant extract is able to reverse AD symptoms adequately. In the present study, Tamarix gallica (TG), a naturally occurring plant known for its strong antioxidative, anti-inflammatory and anti-amyloidogenic properties, was evaluated on homocysteine (Hcy) induced AD-like pathology and cognitive impairments in rats. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Till now, a number of natural plant extracts have shown the ability to reduce tau hyperphosphorylation and the formation of Aβ deposits. We have found that Moringa oleifera (MO), Tamarix gallica (TG), Codonopsis pilosula polysaccharide (CPPs) and Ginkgo biloba extract EGb761 can attenuate memory deficits in AD animal model [83][84][85][86] . These natural plant extracts have the ability to decrease tau phosphorylation and increase PP2A activity but the exact mechanism is unclear.…”
Section: Natural Plant Extractsmentioning
confidence: 99%
“…Till now, a number of natural plant extracts have shown the ability to reduce tau hyperphosphorylation and the formation of Aβ deposits. We have found that Moringa oleifera (MO), Tamarix gallica (TG), Codonopsis pilosula polysaccharide (CPPs) and Ginkgo biloba extract EGb761 can attenuate memory deficits in AD animal model [83][84][85][86] . These natural plant extracts have the ability to decrease tau phosphorylation and increase PP2A activity but the exact mechanism is unclear.…”
Section: Natural Plant Extractsmentioning
confidence: 99%
“…In adult animals, HHC was shown to induce some mitochondria dysfunction and ultrastructural changes in the hippocampus and cortex [ 81 ]. The treatment of adult rats with Hcy led to significant reduction in the number of neuronal cells, degradation of their synapses and dendritic spines, indicating Hcy-associated neurodegeneration [ 82 ]. Furthermore, methionine-enriched diet was shown to alter the volume of adult rat CA1 hippocampus, astroglial activation, and swelling of soma and nuclei of neurons [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have established a sporadic AD rat model through inducing hyperhomocysteinemia in rats. These rats exhibit typical AD-like pathogenesis such as tau hyperphosphorylation, Aβ overproduction, PP2A inhibition, and cognitive deficits [35,36,[43][44][45][46]. To explore the effect of SMAPs in AD model in vivo, HHcy rat model was established after 14 days injection of Hcy (400 μg/kg/day) via the vena caudalis, together with (preventive) or followed with the treatment of DBK-1160 (35 mg/kg, twice a day) or SCR-1693(1 mg/kg/day, treatment positive control) ( Table 2 and Fig.…”
Section: Smap Ameliorates Memory Deficits In Hhcy Ratsmentioning
confidence: 99%